Socioeconomic Status, Personality Traits, Coping Styles, and Mental Health of the Parents of Children with Autism Spectrum Disorder - A. R. Shafiee Kandjani, MD; S. Shafiee; S. Vatankhah; M. Farvareshi, Ph.D. (خانواده و پژوهش, 2020)
Autism is a chronic psychiatric disorder in which social relatedness is profoundly affected. The parents of afflicted children as the main caregivers mostly suffer from the situation. This study aimed at investigating the economic status, social status, coping styles, personality traits and mental health in the parents of children with autism. This cross-sectional, descriptive-analytic study was carried out among the parents of children with autism spectrum disorder in Tabriz.  In 2018-19 school year, ninety parents whose children were diagnosed by a psychiatrist according to DSM.5 criteria were recruited through convenience sampling method. The instruments included NEO Questionnaire, Socioeconomic Status Questionnaire, Coping Styles Questionnaire (Billings and Moos) and SCL-25. The data were analyzed using descriptive statistics and analysis of variance with SPSS-16 software. The parents had a low socioeconomic status, a moderate degree of mental difficulties, but they were responsible and accountable for their performance. In addition, they had problem-oriented coping styles. The attention of health system policymakers and therapists to economic problems and mental health of such parents is mandatory.